PERDEBATAN DAERAH PERTAMA MASUKNYA ISLAM DI INDONESIA - Abdul Gani Jamora Nasution; Novita Sari Nasution; Rizka Rahman Tanjung; Yunita Azhari (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The process of the entry of Islam into Indonesia through different processes, namely through trade, marriage, education, and politics. Islam first appeared in Indonesia in the 7th century AD, the arrival of Islam in Indonesia in various regions was not carried out simultaneously. There are four theories about the entry of Islam into Indonesia which have generated debate, including (1) Indian theory, (2) Arab theory, (3) Persian theory, and (4) Chinese theory. Through this theory, each area explains the differences in the first arrival of Islam in Indonesia. The history of the spread of religions, especially Islam, Christianity, Hinduism and Buddhism in Indonesia, begins with Barus. Especially for Muslims, it is evident from the Mahligai site and the Papan Tinggi site which spread Islam around the 5th century AD. Further developments followed which reached across the archipelago via the Middle East via Central Tapanul. Explanation as well as debate to improve the zero point of Islam in Barus. The process of the arrival of Islam in Indonesia, especially to Barus, Sumatra and the Archipelago in general, is very closely related and begins with the journey of Arab merchants who stop at Barus.